A CASE OF FULMINANT DEVELOPMENT AND PROGRESSION OF HEART FAILURE IN HEART AMYLODOSIS - A. L. Bobrov; A. N. Kulikov; E. V. Gorokhova; S. D. Rud’; L. L. Bobrov (Российский кардиологический журнал, 2016)
A CASE OF FULMINANT DEVELOPMENT AND PROGRESSION OF HEART FAILURE IN HEART AMYLODOSIS.